Synthesis and structural characterization of dinuclear tellurolate palladium(II) complexes. (8th January 2015) - Back, Davi; Manzoni de Oliveira, Gelson; Schulz Lang, Ernesto
Graphical abstract: The synthesis and the structural characterization of the tellurolate–palladium complexes [PdCl(μ-TePh)PPh2 Py]2 and [PdCl(μ-TePh)PPh3 ]2 are described. Although no PdPd interactions were observed, the tellurium atoms attain secondary bonds with a covalent character. Abstract: Bis(diphenyl-2-pyridylphosphine)palladium(II) dichloride and bis(triphenylphosphine)palladium(II) dichloride react with (PhTe)2 Hg in THF to give the binuclear complexes with tellurolate bridges [PdCl(μ-TePh)PPh2 Py]2 (1 ) (Ph = phenyl; Py = 2-pyridyl) and [PdCl(μ-TePh)PPh3 ]2 (2 ). Although no PdPd interactions were observed, the tellurium atoms in both complexes attain secondary bonds with a covalent character.